Pilot Study for Investigating the Cyclic Response of the Recentering Bridge Bearing System Combined with the Friction Damper - Jong Wan Hu; Yong-il Cho (Advances in Materials Science and Engineering)
The bridge bearing is one of the component members which provide resting supports between piers and decks. The bridge bearing is intended to control longitudinal movement caused by traffic flow and thermal expansion, thereby reducing stress concentration. In high seismicity area, the bridge bearing has been utilized as the base isolation system to mitigate acceleration transferred from the ground. Although the existing bridge bearing installed between superstructure and substructure provides extra flexibility to the base of the entire structure, considerable permanent deformation occurs due to lack of recentering capacity after earthquake. It is required to spend extra cost for repairing impaired parts. The bridge bearings integrated with superelastic shape memory alloy (SMA) devices used for upgrading the recentering effect into the friction damper are proposed in this study. The refined finite element (FE) analyses are introduced to reproduce the response of such new structures under cyclic loading condition. The bridge bearing systems that maintain uniform recentering capability are designed with various friction coefficients so as to examine energy dissipation and residual deformation through FE analyses. After observing FE analysis results, optimal design for the recentering bridge bearing system will be proposed to take advantage of energy dissipation and self-centering capacity.